Human RSPO1/R-spondin1 is expressed during early ovary development and augments β-catenin signaling. - Sara Tomaselli; Francesca Megiorni; Lin Lin; Maria Cristina Mazzilli; Dianne Gerrelli; Silvia Majore; Paola Grammatico; John C Achermann (PLoS ONE, 2011)
Human testis development starts from around 42 days post conception with a transient wave of SRY expression followed by up-regulation of testis specific genes and a distinct set of morphological, paracrine and endocrine events. Although anatomical changes in the ovary are less marked, a distinct sub-set of ovary specific genes are also expressed during this time. The furin-domain containing peptide R-spondin1 (RSPO1) has recently emerged as an important regulator of ovary development through up-regulation of the WNT/β-catenin pathway to oppose testis formation. Here, we show that RSPO1 is upregulated in the ovary but not in the testis during critical early stages of gonad development in humans (between 6-9 weeks post conception), whereas the expression of the related genes WNT4 and CTNNB1 (encoding β catenin) is not significantly different between these tissues. Furthermore, reduced R-spondin1 function in the ovotestis of an individual (46,XX) with a RSPO1 mutation leads to reduced β-catenin protein and WNT4 mRNA levels, consistent with down regulation of ovarian pathways. Transfection of wild-type RSPO1 cDNA resulted in weak dose-dependent activation of a β-catenin responsive TOPFLASH reporter (1.8 fold maximum), whereas co-transfection of CTNNB1 (encoding β-catenin) with RSPO1 resulted in dose-dependent synergistic augmentation of this reporter (approximately 10 fold). Furthermore, R-spondin1 showed strong nuclear localization in several different cell lines. Taken together, these data show that R-spondin1 is upregulated during critical stages of early human ovary development and may function as a tissue-specific amplifier of β-catenin signaling to oppose testis determination.